2023
DOI: 10.1186/s12891-023-06348-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative simulation on the reduction quality and clinical outcomes of open reduction and internal fixation for complex proximal humerus fractures

Abstract: Purpose Proximal humerus fractures (PHFs) are common. With the development of locking plates, open reduction and internal fixation (ORIF) of the proximal humerus can provide excellent clinical outcomes. The quality of fracture reduction is crucial in the locking plate fixation of proximal humeral fractures. The purpose of this study was to determine the impact of 3-dimensional (3D) printing technology and computer virtual technology assisted preoperative simulation on the reduction quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Wang and colleagues [ 22 ] showed that pre-contouring plates with the assistance of 3D printing technology accurately fit the humeral shape, resulting in an average Constant score of 76.8 at the 12-month follow-up. Wu et al [ 23 ] conducted a retrospective study on the treatment of PHFs. They divided patients into two groups based on whether 3D printing technology was used for preoperative simulation, and found that the simulation group had shorter operation times and less intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and colleagues [ 22 ] showed that pre-contouring plates with the assistance of 3D printing technology accurately fit the humeral shape, resulting in an average Constant score of 76.8 at the 12-month follow-up. Wu et al [ 23 ] conducted a retrospective study on the treatment of PHFs. They divided patients into two groups based on whether 3D printing technology was used for preoperative simulation, and found that the simulation group had shorter operation times and less intraoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of ORIF in elbow fractures is to re-align and stabilise the joint, which is crucial for enabling early mobilisation and fostering optimal functional recovery. 3,4 This surgical approach is instrumental in facilitating the healing process by ensuring proper alignment of bone fragments and securing them, which is essential for early joint movement and reducing risks such as joint stiffness and muscle atrophy. While ORIF is a critical surgical intervention for elbow fractures, aimed at restoring normal anatomy and ensuring joint stability for optimal functional recovery, this technique is not without its challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Open reduction and internal fixation (ORIF) have emerged as a pivotal surgical technique for these injuries, focusing on restoring the elbow joint's normal anatomy and ensuring its stability. The main goal of ORIF in elbow fractures is to re‐align and stabilise the joint, which is crucial for enabling early mobilisation and fostering optimal functional recovery 3,4 . This surgical approach is instrumental in facilitating the healing process by ensuring proper alignment of bone fragments and securing them, which is essential for early joint movement and reducing risks such as joint stiffness and muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%